Т.ҚАЙЫПБЕРГЕНОВТЫҢ «КӨЗДИҢ ҚАРАШЫҒЫ» РОМАНЫНДА ТУБАЛАЎШЫЛЫҚ ДӘЎИРИ ҲАҚЫЙҚАТЛЫҒЫН СӘЎЛЕЛЕНДИРИЎДЕ ЖАБЫҚ КЕҢИСЛИКТИҢ ОРНЫ - Сагидуллаева, Жамила Нурыллаевна (FAN va JAMIYAT, 2026)
In this article, using the example of T. Kaipbergenov’s novel "The Apple of the Eye", the role of the social chronotope in reflecting the reality of the "Era of Stagnation" is considered. The artistic and aesthetic function of such types of enclosed spaces as sovkhoz (a state farm), a farm, a garage, an office, a house, a room, and a cemetery in creating a social chronotope and conveying the flavor of the era is analyzed.